Betty before X - Shabazz, Ilyasah (Farrar Straus Giroux, 2018)
"Raised by her aunt until she is six, Betty, who will later marry Malcolm X, joins her mother and stepfamily in 1940s Detroit, where she learns about the civil rights movement"--Provided by publisher.